Modern approach to diagnosis of inherited platelet function disorders - Majda Benedik Dolničar; Tina Benedejčič; Lidija Kitanovski; Janez Jazbec; Alenka Trampuš Bakija (Zdravniški Vestnik, 2016)
Inherited platelet function disorders (IPFD) comprise a heterogeneous group of diseases. Their real frequency is probably underestimated as in many patients with excessive subcutaneous and mucosal bleedings the disorder has not been recognized. The presented diagnostic recommendations are based on a systematic review of the scientific literature and describe the role of platelets in the clotting process and the most common congenital disorders of platelet function. A diagnostic algorithm for clinical and laboratory stepwise management of patients with IPFD is presented.